2009
DOI: 10.1002/jnr.22057
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid‐β interrupts the PI3K‐Akt‐mTOR signaling pathway that could be involved in brain‐derived neurotrophic factor‐induced Arc expression in rat cortical neurons

Abstract: The deposition of amyloid-beta (Abeta) contributes to the pathogenesis of Alzheimer's disease. Even at low levels, Abeta may interfere with various signaling cascades critical for the synaptic plasticity that underlies learning and memory. Brain-derived neurotrophic factor (BDNF) is well known to be capable of inducing the synthesis of activity-regulated cytoskeleton-associated protein (Arc), which plays a fundamental role in modulating synaptic plasticity. Our recent study has demonstrated that treatment of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(58 citation statements)
references
References 61 publications
4
54
0
Order By: Relevance
“…Signaling pathways other than the CaMKIV-CREB pathway could be involved in the interactive effects of stress, A and nicotine. For example, multiple studies have demonstrated the involvement of the phosphatidylinositol 3-kinaseAkt (PI3K/AKT) [102,103] and Janus kinase 2 (JAK2)/ signal transducer and activator of transcription 3 (STAT3) [104] signal transduction pathways in A -induced cell death and memory loss. These pathways are also involved in cell response to oxidative stress [e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Signaling pathways other than the CaMKIV-CREB pathway could be involved in the interactive effects of stress, A and nicotine. For example, multiple studies have demonstrated the involvement of the phosphatidylinositol 3-kinaseAkt (PI3K/AKT) [102,103] and Janus kinase 2 (JAK2)/ signal transducer and activator of transcription 3 (STAT3) [104] signal transduction pathways in A -induced cell death and memory loss. These pathways are also involved in cell response to oxidative stress [e.g.…”
Section: Discussionmentioning
confidence: 99%
“…mTOR is the master regulator of autophagy (52,70). The signaling cascade PI3K/Akt/mTOR is inhibited by A␤ (71). Trib3 inhibits the Akt/mTOR axis and leads to autophagy in human glioma cells (7).…”
Section: Discussionmentioning
confidence: 99%
“…Sublethal doses of b-amyloid 42 down-regulate BDNF expression in cultured cortical neurons and impair BDNF intra-cellular trafficking (Poon et al 2011). Another important effect of b-amyloid 42 in cultured neurons is the impairment of BDNF-induced Arc expression (Chen et al 2009;Echeverria et al 2007;Wang et al 2006). This is an immediate early response gene that is rapidly activated by BDNF and whose product, Arc protein, is thought to be an important mediator of BDNF effects in synaptic plasticity and long-term potentiation formation (Bramham et al 2008).…”
Section: Cellular and Animal Models Of Admentioning
confidence: 98%